Estimation of Heat Flow Using a Bottom Simulating Reflection Based on 3D Seismic Data, West Africa - Le, Anh Ngoc (Indonesian Journal on Geoscience, 2021)
A Bottom Simulating Reflection (BSR) has been identified using 3D seismic data from the Cameroon continental slope margin. The BSR covers an area of c. 350 km2 in water depths ranging between 940 m to 1,750 m across an area characterized by high- and low-gradient slopes, gullies, scours, and fans. The thickness of the Gas Hydrate Stability Zone (GHSZ) is ~100 - 250 m, assuming an average velocity of 1,800 m/s. Pockmarks are intensively developed across the slope and most of them are observed in the BSR area. Geothermal estimation is based on hydrate stability conditions for pure methane - seawater system, hydrostatic pressure model, and a range of P-wave velocity models for the GHSZ, ranging from 1,600 -1,800 to 2,000 - 2,200 m/s. Geothermal gradient is calculated showing the range and distribution of thermal gradients in the BSR area from 0.046 C/m to 0.094 oC/m with assumed GHSZ velocity of 1,800 m/s. Thermal gradient anomalies have been observed in association with gullies, vertically stacked channels and in some individual pockmarks. The highest anomalies of 0.08 C/m – 0.094 C/m are found in the depression areas of pockmark trains, within seafloor gullies. These positive anomalies are most likely controlled by active or recently active fluid advection and expulsion through the Cameroon slope.